The Attributes of Leadership Styles Influence on Employee Performance mediated by Job Satisfaction: Evidence on Textile and Shoe Industry in Salatiga City - Sumarno , Ari Pitoyo; Ariadi, Gede (Universitas Pendidikan Ganesha, 2023)
This research aimed to examine the effect of transactional and transformational leadership styles on employee performance mediated by job satisfaction. This research was followed by 100 employees in the production division of a textile and shoe company in Salatiga. This research used social exchange theory and PLS-SEM (Partial Least Square-Structural Equation Method) analysis. The results of this research indicated that job satisfaction has a significant influence in mediating the relationship between transformational leadership and employee performance, while transactional leadership has less significant influence. Therefore, the results of this research could be used as a support for Social Exchange theory which focuses on employee interaction in increasing motivation to provide maximum performance and develop good relations with superiors.